Perceptions of Class XII Students at SMA Negeri 1 Teras Boyolali Towards Arts and Culture Subjects in the Merdeka Curriculum - Aditia, Bahrurrizqi; Aditia, Rafinita (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2024)
The demands of the current era encourage the world of education to become more innovative. Implementing an independent curriculum is one form of implementation and answer to these challenges. However, the use of the merdeka curriculum that occurred in 2021 invited many types of opinions, one of which was from students. This research aims to describe the perceptions of class 12 students at SMA Negeri 1 Teras Boyolali towards arts and culture subjects in the context of the Independent Curriculum. The research method used is qualitative, with a focus on the interpretation of social phenomena based on interview data, observation and documentation. The research results show that students' enthusiasm for learning in arts and culture subjects varies, influenced by internal and external factors such as art experience, views on the relevance of the subject, and teachers' teaching methods. The implementation of the Independent Curriculum provides new opportunities for arts and culture learning experiences, but also gives rise to diverse opinions about its relevance in the modern era. The role of teachers as facilitators in developing students' interests and talents is recognized as important, but the Pancasila Student Profile program also raises questions about the relevance of arts and culture subjects. In conclusion, students' opinions about arts and culture subjects in the Independent Curriculum are influenced by various factors, and this understanding can make an important contribution to future curriculum development.